Gilbert-Charles Picard (1913-1998) and the Religions de l’Afrique Antique - López Gómez, José Carlos (Universidad Carlos III de Madrid, 2021)
This article analyses, from a historiographic perspective, the most important aspects of Charles-Gilbert Picard’s work on the religious world of the populations inhabiting the Maghreb during the Punic and Roman periods, with special emphasis on his magnum opus on the subject, Les religions de l’Afrique Antique. In doing so, I have attempted to explain the evolution in thought of an author who was one of the most prominent scholars of the ancient religions in North Africa between the end of the Second World War and the process of decolonisation of the Maghreb.
Keywords: Picard, Gilbert- Charles - Crítica e interpretación; Ancient religion; Historiography; Punic; Roman